2014
DOI: 10.7314/apjcp.2014.15.14.5787
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Ventilator-Associated Pneumonia in Cancer Patients

Abstract: Background: With increasing survival periods and diversification of treatment methods, treatment of critically ill cancer patients has become an important factor influencing patient prognosis. Patients with cancer are at high risk of infections and subsequent complications. This study investigated the incidence and factors contributing to the development of ventilator-associated pneumonia (VAP). Materials and Methods: This retrospective study investigated the incidence of VAP and factors leading to infection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…In agreement with several previous studies, this study showed that the limitation of positional changes,[21] increase in age,[22] and also being overweight[23] are risk factors of developing VAP.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with several previous studies, this study showed that the limitation of positional changes,[21] increase in age,[22] and also being overweight[23] are risk factors of developing VAP.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, VAP increased the MV time and prolonged the ICU length of stay. This is in agreement with the ndings of many studies, indicating that VAP imposed a great burden on patients [11,72,73]. This meta-analysis had some limitations.…”
Section: Discussionsupporting
confidence: 91%
“…Identified risk factors for VAP in cancer patients include age (≥65 years), surgery, and tracheostomy. [ 38 ] On the contrary, IHM was lower when principal diagnosis was cranial hemorrhage or cranial or spinal fracture. Cinotti et al [ 39 ] found that among patients suffering from subarachnoid hemorrhage, longer ICU stay and time with mechanical ventilation increased the risk of VAP, but not of mortality.…”
Section: Discussionmentioning
confidence: 99%